FACTORS INFLUENCING INTEREST IN USING DANA AND OVO E-WALLETS IN THE MILLENNIAL GENERATION - Antoni, Syafrul (Accounting Department, Politeknik Negeri Bandung, 2023)
Abstract This study aims to find out whether trust, social influence, and convenience affect students' interest in using Dana and Ovo e-wallets for FEBI students, 2019 IAIN Kerinci. This research is a quantitative research. Source of data used is primary data. The population used in this study were students of the 2019 Islamic Faculty of Economics and Business at IAIN Kerinci. The sampling technique used in this study is snowball sampling which is taken in sequence, starting from a small sample size that gets bigger and so on, so that the number of samples increases. It's like a snowball rolling, the longer it gets bigger, the more respondents you get, namely 40 respondents. The data collection technique used was a questionnaire with a sample of 40 people. The results of the partial research (t test) for the trust variable affect interest in using Dana and Ovo e-wallets. The social influence variable influences the interest in using the Dana and Ovo e-wallets. The convenience variable has no effect on interest in using Dana and Ovo e-wallets. while simultaneously trust, social influence and convenience Keywords: trust, social influence and convenience and interest